2022
DOI: 10.1021/acsabm.2c00252
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Bacterial Targeting by a Thiazolyl Benzenesulfonamide and Octaarginine Peptide Complex

Abstract: A brominated thiazolyl benzenesulfonamide (BTB) derivative is conjugated with the cell-penetrating peptide octaarginine (R8) in an effort to construct innovative antibacterial products. The noncovalent complex of BTB and R8 is characterized by Fourier transform infrared (FTIR) spectroscopy, which indicates hydrogen bonding between the two constituents. Attachment of the peptide moiety renders aqueous solubility to the hydrophobic benzenesulfonamide drug and bestows bactericidal activity. Confocal imaging in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…HPLC is often used for purification of the CPP-s post-synthesis, but it can also be used to characterize CPPcargo, and UPLC methods can be used to characterize the stability of CPP-cargo by detecting its degradation. Spectroscopy-based methods such as Fourier Transform infrared spectroscopy (FTIR) was used to characterize R8cargo complexes (Ratrey et al, 2022), and the presence of CPPs in the gold NPs was confirmed by this method (Boussoufi et al, 2018).…”
Section: Association and Dissociation Of Cpp-cargomentioning
confidence: 99%
See 1 more Smart Citation
“…HPLC is often used for purification of the CPP-s post-synthesis, but it can also be used to characterize CPPcargo, and UPLC methods can be used to characterize the stability of CPP-cargo by detecting its degradation. Spectroscopy-based methods such as Fourier Transform infrared spectroscopy (FTIR) was used to characterize R8cargo complexes (Ratrey et al, 2022), and the presence of CPPs in the gold NPs was confirmed by this method (Boussoufi et al, 2018).…”
Section: Association and Dissociation Of Cpp-cargomentioning
confidence: 99%
“…In addition to RBC, the interactions or leakiness can be investigated on more artificial setups, such as large unilamellar vesicles (LUV) and giant unilamellar vesicles (GUV) (Ratrey et al, 2022). By enclosing fluorescent dyes into the vesicles, the leakage of these detectable substances can be measured after interactions between the CPP-cargo and vesicles.…”
Section: Interactions With (Cell and Artificial) Membranesmentioning
confidence: 99%